2017
DOI: 10.1016/j.surg.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Calpain inhibition decreases inflammatory protein expression in vessel walls in a model of chronic myocardial ischemia

Abstract: Introduction Emerging data suggests a link between calpain activation and the enhanced inflammatory response of the cardiovascular system. We hypothesize that calpain activation associates with altered inflammatory protein expression in correlation with the pro-inflammatory profile of the myocardium. Our pig hypercholesterolemic model with chronic myocardial ischemia will be treated with calpain inhibitors (CI) to establish their potentials to improve cardiac function. Methods Yorkshire swine, fed a high cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Additionally, calpain activation targets proteins in mitochondria that compromise mitochondrial function, resulting in excessive ROS generation and oxidative stress. 18,82,83 This study showed that a CI or capn1 deletion inhibit diabetes-induced increases in the expression of iNOS and ICAM-1 in the retina. Expression of both proteins is regulated by NF-kB, subsequent to degradation of IkBa, and translocation of NF-kB to nucleus.…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, calpain activation targets proteins in mitochondria that compromise mitochondrial function, resulting in excessive ROS generation and oxidative stress. 18,82,83 This study showed that a CI or capn1 deletion inhibit diabetes-induced increases in the expression of iNOS and ICAM-1 in the retina. Expression of both proteins is regulated by NF-kB, subsequent to degradation of IkBa, and translocation of NF-kB to nucleus.…”
Section: Discussionmentioning
confidence: 75%
“…NFKB, IL1B, TNF, TLR4, and ICAM1 as inflammatory markers play important roles in inflammatory signaling by aiding the activation of NFKB. Moreover, almost all studies on ischemia-associated heart injury demonstrated that the inhibition of NF-kappa B activity could attenuate inflammation-associated injury and improve cardiac function . In this present study, a model of cardiomyocyte hypoxia/reoxygenation pathology was first constructed.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, almost all studies on ischemia-associated heart injury demonstrated that the inhibition of NF-kappa B activity could attenuate inflammation-associated injury and improve cardiac function. 54 In this present study, a model of cardiomyocyte hypoxia/reoxygenation pathology was first constructed. qRT-PCR detection analysis concluded that NFKB, IL1B, TNF, TLR4, and ICAM1 were significantly upregulated in the model group, which further suggested that the cardiomyocyte injury model was highly activated.…”
Section: Discussionmentioning
confidence: 99%
“…Two Yorkshire swine (male and female; Tufts University, Medford, MA, USA), aged 8 to 10 weeks and weighing between 22 and 25 kg at the time of the initial procedure, were used. This pilot study was designed to assess technical feasibility using an established model of chronic myocardial ischemia developed by Dr. Sellke as previously described [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. To induce chronic ischemia, a small left thoracotomy was performed, the pericardium was opened, and an ameroid constrictor composed of hygroscopic casein material cased in titanium (Research Instruments SW, Escondido, CA, USA) was sized and placed around the proximal left circumflex (LCX) coronary artery (Figure 2B).…”
Section: Animal Methodsmentioning
confidence: 99%